KNOWLEDGE AND PRACTICES OF PARENT OR RESPONSIBLE IN CARE PRESCHOOL - Ethel Bastos da Silva; Luana Possamai Menezes; Bruna Stamm; Suelen Fernandes Hempel; Lílian Signor Dalla Nora (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976926282 Aim: to know the knowledge and practices of parents or guardians in hygiene and health care of preschool children who study in kindergartens in Palmeira das Missões/RS. Method: descriptive, explanatory research with qualitative approach. Data collection was done through questionary with semi-structured questions, composed of socio demographic information and with matters related to hygiene habits and daily care of children and their families. For data analysis, a thematic type of Content analyses was adopted in which two thematic axes emerged. Results: it was evident with the study that parents' and guardians' knowledge and practices on hygiene are associated with the families' culture and economic condition. Conclusion: it is suggested closer approximation of nursing and health staff with families and Kindergarden Schools aiming at promoting health education actions.